Capacity for Forestry Research in the Southern African Development Community - Kowero, G.S.; Spilsbury, M.J. (1997)
In 1995 a survey of research capacity was conducted at institutions undertaking forestry-related research in the SADC countries. This document presents a review of the methods available for the assessment of research capacity and summarizes previous efforts to assess research capacity in the region. The methodology adopted makes use of common indicators thereby allowing comparisons across institutions. The results of the survey are discussed and re-emphasize the need to prioritize manpower recruitment, training and development; only about half of the scientists researching forestry and related issues have sufficient training and scientific exposure. The management of research is another area requiring urgent attention in order to minimize the negative impacts of many of the economic and other externalities afflicting research in the region. About 17% and 28% of the institutions surveyed allocate more than 20% of their budgets and staff time respectively, to user groups. This raises questions on how research priorities are formulated and the relevance of the research in progress. There is considerable interaction between institutions in the region, but how this can translate into coordinated collaborative activities remains unclear. Although the indicators for the various research capacity parameters do not capture the totality of capacity implications, they provide useful insights on the existing local capacity to undertake forestry research in eastern and southern Africa.